Multi-mission remote sensing of low concentration produced water slicks - Johansson, Malin; Skrunes, Stine; Brekke, Camilla; Isaksen, Hugo (VDE Verlag, 2021)
Source at https://www.vde-verlag.de/proceedings-de/455457056.html . Produced water is legally released from oil platforms and often detected by oil spill detection services despite their low oil concentrations. Using fully-polarimetric RADARSAT-2 and dual-polarimetric Sentinel-1 data we investigate their synthetic aperture radar (SAR) characteristics. Detectability ranges within the SAR and optical Sentinel-2 and PlanetScope images are assessed and compared to in-situ data from the Brage platform. Given similar releases and environmental conditions are the detected slicks in optical images smaller and shorter than those observed in SAR images. The damping ratios and polarization differences are similar to thicker mineral oil slicks, though with higher within slick variance.